The Development of Tourism Object of Love Beach in Cikoang, Takalar Regency - Musin, Mujali (UNM Geographic Journal, 2018)
This study aims to determine 1) the factors of geography that support the development of coastal tourism in the village Cikoang love.2) Obstacles encountered in the development of beach tourism in the village Cikoang love.3) The extent SWOT analysis of the development of coastal tourism in the village love Cikoang in the future.The population of tourists, managers and the public.The data presented in the form of primary data taken from the questionnaire "Development Geography Tourism Object Love Beach In the village of the District CikoangMangarabombangTakalar".Samples were taken by accidental sampling method and purposive sampling method.Analysis of the data used is descriptive qualitative analysis and SWOT analysis.The results showed that the development of appropriate strategies in the development of business attraction Love Beach is a strategy Weaknesses - Opportunities.The conclusion among other aspects of geography that supports the development of tourism, among others: the location, morphology, hydrology, land pengggunaan, tourists, income level, education, employment, and facilities.Additionally necessary facilities and infrastructure development, promotional activities more aggressively again, as well as to cooperate with relevant parties in terms of the development of Love beach tourism